(untitled) - Pavitt, Keith (New York, 1981)
Contents: Innovative Activities and Export Shares: some Comparisons; Technical Change in the Defence Industry Mary Kaldor; Innovation in Textile Machinery Roy Rothwell; Forklift Trucks Peter Senker
Keywords: Technological innovations,Đổi mới công nghệ; Economic aspects,Khía cạnh kinh tế; Great Britain,Anh